Extending European energy efficiency standards to include material use: an analysis. (28th May 2018) - Scott, Kate; Roelich, Katy; Owen, Anne; Barrett, John
ABSTRACT: Existing international emissions reduction policies are not sufficient to meet the internationally agreed objective of limiting average global temperature rise to 'well below' two degrees, resulting in an emissions gap. Materials – such as aluminium, cement, paper, plastics and steel – act as a carrier of industrial energy that allows, through trade, the transfer of embodied emissions between sectors and countries. However, the use of materials has been overshadowed by policies focusing on energy efficiency improvements and deployment of a low carbon energy supply. This article argues that policies based on material and product demand can support domestic climate change mitigation and reduce the emissions gap, yet there is little obvious integration between climate and material efficiency policies. The article investigates current 'emissions flows' through the EU economy and how much of these are captured and excluded from existing EU climate policies. We analyse the potential increase in emissions coverage that would be achieved by extending EU directives that currently target the energy use of products (cars, buildings and appliances) in operation, to include the emissions required to produce the goods (i.e. embodied emissions). The analysis shows that a greater integration of material efficiency strategies within climate change mitigation policy could significantly increase the emissions coverage of existing product policies. Key policy insights Consumption is a key driver of emissions and demand reduction is an important policy option in reducing emissions, at least in the short-term, to reduce the risks of a longer-term reliance on technology breakthroughs and while the EU carbon price remains low. Emissions embodied in material-intensive manufactured products consumed in the EU represent the equivalent of over 40% of EU production emissions, offering significant scope for emissions reductions along product supply chains. Consumption measures that target the use of materials and products offer complementary mitigation options to low carbon energy supply technologies alongside costs savings. Existing EU policies addressing the energy efficiency of products can be used to scale up material efficiency measures.